2005
DOI: 10.1093/hmg/ddi077
|View full text |Cite
|
Sign up to set email alerts
|

FMRP interferes with the Rac1 pathway and controls actin cytoskeleton dynamics in murine fibroblasts

Abstract: Fragile X syndrome, the most common form of inherited mental retardation, is caused by absence of FMRP, an RNA-binding protein implicated in regulation of mRNA translation and/or transport. We have previously shown that dFMR1, the Drosophila ortholog of FMRP, is genetically linked to the dRac1 GTPase, a key player in actin cytoskeleton remodeling. Here, we demonstrate that FMRP and the Rac1 pathway are connected in a model of murine fibroblasts. We show that Rac1 activation induces relocalization of four FMRP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
168
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(177 citation statements)
references
References 66 publications
7
168
1
1
Order By: Relevance
“…Interestingly, in this regard, is the observation that Rac1 activation in murine fibroblasts leads to relocalization of four FMRPinteracting proteins (CYFIP1, FXR1P, NUFIP and 82-FIP) to actin-containing domains [14]. Taken together, these data suggest a model in which CYFIP and FMRP act together in a dynamic signaling complex to regulate actin dynamics and protein translation, processes that are critical for neuronal morphogenesis and connectivity.…”
Section: Fragile-x Syndromementioning
confidence: 89%
“…Interestingly, in this regard, is the observation that Rac1 activation in murine fibroblasts leads to relocalization of four FMRPinteracting proteins (CYFIP1, FXR1P, NUFIP and 82-FIP) to actin-containing domains [14]. Taken together, these data suggest a model in which CYFIP and FMRP act together in a dynamic signaling complex to regulate actin dynamics and protein translation, processes that are critical for neuronal morphogenesis and connectivity.…”
Section: Fragile-x Syndromementioning
confidence: 89%
“…FMRP, an RNA binding protein involved in mRNA translation, splicing, and mRNA transport in the cell, was identified as a G-quadruplex interacting protein (77)(78)(79). FMRP binds tightly to G-quadruplexes in the 5Ј-UTRs of protein phosphatase 2A catalytic subunit and MAP1B (microtubule-associated protein 1B), and it was suggested that this interaction represses translation of both mRNAs (77,80). Furthermore, it was demonstrated that the FMRP-G-quadruplex repressor in the MAP1B 5Ј-UTR was destabilized by an increased FMRP concentration, suggesting that the variation of FMRP concentration in response to neuronal stimulation might act as a regulatory switch from translational repressor to a translational activator (43).…”
Section: Discussionmentioning
confidence: 99%
“…CYFIP2 and CYFIP1 (located on human chromosomes 5q33.3 and 15q11, respectively) encode highly homologous, ubiquitously expressed, and evolutionarily conserved adaptor/scaffolding proteins that lack any known functional domains or motifs. 20 To date, both CYFIP2 and CYFIP1 have been implicated by functional and biochemical studies as regulatory scaffolding proteins for at least four independent complexes associated with the Rac pathway-the FMR mRNP complex important for mRNA translational control; 20,21 and the WAVE1, WAVE2, and WAVE3 complexes each important for ARP2/3 mediated actin nucleation and regulation of cell motility. 14,22,23 While CYFIP1 does not appear to be a p53-regulated gene based upon our real-time PCR data, our data do identify CYFIP2 as a p53-regulated gene.…”
Section: Discussionmentioning
confidence: 99%